STUDIES ON THE EFFECT OF SUPPLEMENTATION OF AREA SPECIFIC MINERAL MIXTURE ON MICRO MINERAL STATUS AND CYCLICITY IN POST-PARTUM ANESTROUS COWS - JANA, SONALI; VERMA, M S; WADHWA, D; SHARMA, K B; KUMAR, R (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to identify possible trace mineral deficiencies causing anestrus andprolonged post-partum anestrus and evaluate the effect of strategic supplementation of Area Specific MineralMixture (ASMM) in these cases. The animals selected for study were categorized under three groups GroupI- Control animals (anestrous cows of 90 days and above), Group II- Anestrous animals (anestrous of 90days and above) and Group Ill- Pleuriparous animals (8 to 9 months of gestation) from Livestock Farm ofCSKHPKV, Palampur consisting of 10 animals in each group. Parallel study was also conducted on animalsfrom nearby villages of Panchrukhi block of District Kangra in the state of Himachal Pradesh consisting of 4,11 and 6 cows in Group I, II and Ill respectively. The animals of Group II and Group Ill were supplementedwith specially formulated Area Specific Mineral Mixture @ 50 gm/animal/day until the animals attained estruswhereas animals of Group I were kept as control. Anestrous group of cows from field showed a significant(p
Keywords: Anestrous; Post-partum anestrous; mineral mixture supplementation; trace minerals